Assessment of the variation of the physicochemical quality of groundwater in Dasmariñas, Cavite and its suitability for drinking purpose using GIS and water quality index - Rubio, Rojeena Gail R. (College of Engineering, University of the Philippines Diliman, 2017)
This study examines the changes in the physical and chemical quality of groundwater in Dasmariñas, Cavite from 2009 to 2016, using geographic information system (GIS). It also assesses the suitability of the groundwater for drinking purpose using Water Quality Index (WQI). Historical groundwater data was gathered from the Dasmariñas Water District (DWD).The water quality parameters include color, turbidity, odor, bicarbonate, carbonate, pH, calcium, magnesium, total hardness, chloride, fluoride, iron, manganese, lead, specific conductance, and total dissolved solids. ArcGIS was used to present the spatial variations of each parameter in maps. One-Sample t-Test was done to evaluate the groundwater quality every year, identifying whether each parameter value meets several water quality standards, namely: Philippine National Standards for Drinking Water (PNSDW) 2007, DENR Administrative Order (DAO) No. 2016-08, World Health Organization (WHO)Guidelines for Drinking Water Quality, Guidelines for Canadian Drinking Water Quality (GCDWQ), and U.S. National Primary and Secondary Drinking Water Regulations (NPDWRs and NSDWRs). The Canadian Council of Ministers of the Environment Water Quality Index (CCME WQI) was used to calculate scores that represent the overall groundwater quality, with corresponding rating categories. The spatial analysis found that concentrations of carbonate, calcium, total hardness, chloride, specific conductivity, and total dissolved solids were found to be low at the south part of the city getting higher towards the north. One-Sample t-Test results show that the PNSDW 2007 and the DAO 2016-08 were not failed throughout the study period, while the WHO Guidelines, GCDWQ, and the US NPDWRs/NSDWRs were failed by at most two parameters at certain periods. The CCME WQI scores computed indicate that groundwater in Dasmariñas is of good to excellent quality based on the PNSDW 2007 and the DAO 2016-08, while of poor to good quality based on the other three water quality standards. Based on the PNSDW 2007 and the DAO 2016-08, which are the standards to be followed in the Philippines, the groundwater in Dasmariñas meets all the regulations for the parameters analy